Utilization of coal bottom ash in bricks / Nor Fadilah Mohamad ... [et al.] - Mohamad, Nor Fadilah; Jumali, Saiful; Zamri, Siti Safawati; Mohd Zaini, Nur Ain Farhana; Mahad, Muhammad Hakim (2018)
Coal combustion products can be categorised into four, which are fly ash, flue-gas desulfurization, bottom ash and boiler slag. These product comprises of combustibles which were embedded during formation of clinkers and stick to hot side walls of a coal burning furnace during the operation of furnace. These products can play an important role in concrete and bricks production. Out of these four, only fly ash and bottom ash are widely used in industry. Fly ash can be described as very fine, powdery material which contain mostly silica as a product from ground coal boiler. Meanwhile, bottom ash has its own shape, angular and coarse particles which are too heavy to carry by smoke formed at the bottom of the coal furnace. Bottom ash currently used as fine aggregate element in concrete which as many advantages towards strength and resistance. Limited application in major areas making bottom ash overlooked as waste material. Despite recycling, an alternative on making bricks with substitution of coal bottom ash is conducted which goes pre treatment and non-pre-treatment. Pre-treatment is done to reduce the content of carbon in coal bottom ash. Pre-treatment process is done by using 'sink and float' method. Addition of coal bottom ash as partial replacement of cement resulted an increase in physical performance which altered the properties of the bricks. Based on the result, the utilisation of coal bottom ash as cement replacement gave positive impact compared to normal bricks. It has been discovered that I 0% of coal bottom ash is the best quantity used as a replacement for cement as well as it recorded the lowest percentage in water absorption. For ultrasonic pulse velocity the result scored in the between the range of lowest and highest value and highest for compressive test. Overall, the bricks produced passed all the standard requirements for industrial purposes. Therefore, coal bottom ash usage as cement replacement paved new way in saving cost expenses and generate a new type of bricks in the future